THE ROLE OF ENVIRONMENTAL MANAGEMENT ACCOUNTING, TECHNOLOGY, AND OPERATIONS STRATEGY IN DRIVING CORPORATE INNOVATION - Meiliyah Ariani; Zulhawati (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The increase in industrial activity in various regions has brought changes both internally and externally. The fact of environmental pollution caused by manufacturing companies in Indonesia underscores the need for a business environment that is able to maintain its business processes and simultaneously implement strategies to maintain going concern and sustainable development. This research aims to develop a model or framework that integrates environmental management accounting, technology, and operating strategies as a way to optimize innovation within the company. The sampling technique used is puposive sampling. The sample size was 229 employees of frozen food  companies in Balaraja District, Tangerang Regency. The analysis method used is multiple linear regression analysis using SPSS 25. Based on the results of the study, it shows that environmental management accounting has a significant positive effect on company innovation. Technology has a significant positive effect on company innovation. Operating strategy has a significant positive effect on the company's innovation